Evaluation of Employment Contentment among Nurses in Critical Care Settings - Fernandes, Filipe (2025)
In Intensive Care Units (ICUs), nurses operate within an environment where data may be interpreted in entropic terms, directly influencing rapid decision-making and strategy formulation, i.e., this high-stakes environment necessitates seamless collaboration between nurses, physicians, and patients, which is vital for the association and consolidation of long-term objectives. Indeed, job satisfaction for nurses in ICUs is a multifaceted issue, influenced by a complex interplay of workplace dynamics, interprofessional relationships, and a variety of social, cultural, economic, and emotional factors which will be examined through detailed questionnaires that probe into general backgrounds and delve into specific domains such as Corporate, Personnel, and methodological approaches to problem solving. These are in alignment with the study’s goals to measure awareness and nurse satisfaction within the challenging yet rewarding ICU setting. Moreover, using Mathematical Logic Programs, the study investigates nurses’ perceptions of their job satisfaction, assessing them against best-case and worst-case scenarios. This examination aims to identify patterns that could inform proactive and remedial strategies. Such problem-solving methodologies uncover avenues to enhance conditions that foster the professional growth of Intensive Care Nurses, integrating systematic planning with empathetic patient care.